Binocular retinal image differences influence eye-position signals for perceived visual direction - Sridhar, Deepika (2012)
Correctly perceiving the direction of a visible object with respect to one’s self (egocentric visual direction) requires that information about the location of the image on the retina (oculocentric visual direction) be combined with signals about the position of the eyes in the head. The Wells-Hering laws that govern the perception of visual direction and modern restatements of these laws assume implicitly that retinal and eye-position information are independent of one another. By measuring observers’ manual pointing responses to targets in different horizontal locations, we show that retinal and eye-position information are not treated independently in the brain. In particular, decreasing the relative visibility of one eye’s retinal image reduces the strength of the eye-position signal associated with that eye. The results can be accounted for by interactions between eye-specific retinal and eye-position signals at a common neural location.